Fácies sedimentares e sistemas deposicionais da Formação Barbalha na região de Nova Olinda, borda norte da Bacia do Araripe - Brito, Lucas Adriano Rodrigues (2023)
This work focuses on the revision of the Barbalha Formation on the northern edge of the Araripe Basin through the analysis of facies, architectural elements, macroscopic provenance and paleocurrents for the definition of depositional systems. The objectives were: a) to interpret depositional systems; b) to understand the stratigraphic positioning of the sedimentary sequence in the context of the post-rift phase of the Araripe Basin. Six sedimentary lithofacies were recognized: clast-supported conglomerates with incipient lodging, massive conglomerates, sandstones with planar cross-stratifications, sandstones with channeled cross-stratifications, sandstones with low-angle cavalcating cross-stratifications, laminated argillites. Four architectural elements were identified: channels, sediment gravity flow, gravel bar bed forms, and sandy bedforms. In addition, 200 clasts from the conglomeratic facies framework and the analysis of paleocurrents measured in 77 sedimentary structures and 207 imbricated clasts were qualified. Thus, this sedimentary package was classified as a longitudinal section of terrigenous alluvial fan systems, presenting its terminal portions (lamitic and sandstone facies), as well as part of the proximal portions (conglomeratic facies filling channels) that stack in a prograded pattern, with overlapping of the conglomerates to the sandstones/argillites without hiatus or unconformities. The change in the water flow regime implies climatic variations, where the climate changed from humid to semi-arid, or tectonic variations, where there was reactivation of edge faults with reactivation of tectonic scarlets, or an association of both. The reactivation, it was concluded that the sedimentary succession studied may be associated with the tectonic events of the post-rift phase of the Araripe Basin, which possibly occurred contemporaneously with the deposition of interlaced alluvial systems from the top of the upper sequence of the Barbalha Formation, interdigitated with the first basal lamite facies of the Crato Formation.